Enhanced performance of natural dye-based halochromic sensor for monitoring the spoilage of packed fish. (2022) - Devarayan, Kesavan; Vaz Motcham, Vinothini; Sukumaran, Monikandon; Marimuthu, Ramar; Anjappan, Hema
Abstract: Fish is a valuable source of nutrients, but it is also perishable. It is nearly impossible to detect the spoilage of packed fish by sensory evaluation. The present study describes use of an halochromic for detecting the deterioration of packaged sardine fish. The halochromic sensor was characterized by SEM, EDS, and CIELAB image processing. Color changes from brownish pink to yellowish green by the sensor indicated the spoilage of the packed fish. Biodegradability and recycle usage of the sensor was also evaluated.